Co-Inoculation of Bacillus spp. for growth promotion and iron fortification in Sorghum - Manasa, Mansani; Ravinder, Polapally; Gopalakrishnan, Subramaniam; Srinivas, Vadlamudi; Sayyed, R. Z.; El Enshasy, Hesham Ali; Yahayu, Maizatulakmal; Tan, Ali Kee Zuan; Kassem, Hazem S.; Hameeda, Bee (Multidisciplinary Digital Publishing Institute, 2021)
Seven Bacillus spp. isolated from the marine water and the rhizosphere of the medicinal plant Coscinium fenestratum were studied to produce plant growth promotion (PGP) traits invitro. Among the seven isolates, MMRH22 and RHPR20 produced copious amounts of PGP traits. Based on the 16S rRNA sequence, the two potent bacterial isolates, RHPR20 and MMRH22, were identified as Bacillus mojavensis and Bacillus cereus, respectively. A compatibility test between the isolates RHPR20 and MMRH22 revealed they are compatible and can be used as a consortium. Both isolates were evaluated for the plant growth promotion and the biofortification of sorghum under greenhouse conditions. Treatments included the application of MMRH22, RHPR20, their consortium (RHPR20 + MMRH22), and an uninoculated control. Inoculation with bacterial cultures resulted in a significant increase in the plant height; the number of leaves; the leaf area; the root, shoot, and leaf weight; and the yield of sorghum at 30 and 60 days after sowing (DAS). The scanning electron micrograph of the sorghum plant roots revealed extensive colonization in the plants treated with the bacterial cultures compared to the uninoculated control. The sorghum grains obtained after final harvest were analyzed for their nutrient content by ICP–OES. The biofortification in sorghum grains was varied and was found to enhance the iron content up to 97%. This study revealed that treatments with microbial consortia enhance plant growth, yield, and iron content, which could combat nutrient deficiencies in plants and humans.